VD_FINDINFO Jug / 2014 / 36 vom 4. Oktober 2013 - VD Tribunal cantonal (2013)
LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, JUGE UNIQUE, CONTRAVENTION | 34 al. 3 LCR, 44 al. 1 LCR, 3 al. 1 OCR, 398 al. 4 CPP (CH), 406 al. 1 let. c CPP (CH), 14 al. 3 LVCPP